Exploring crystals /James Berry. - Berry, James 1933- (London Crowell-Collier Press, 1969)
Describes the nature and properties of several varieties of crystals and their many uses in science and industry. Includes directions for experiments and a glossary of terms.
Bibliography: p. [101]-102.
Keywords: Crystallography -- Juvenile literature; Crystallography